Pt-Ru Catalysts supported on mesoporous carbons for polymer electrolyte membrane fuel cells - Calderon, J. C. (2011)
Pt-Ru electrocatalysts supported on xerogels and CMK-3 ordered mesoporous carbons were synthesized by reduction with formate ions (SFM method). Some of the carbon supports were chemically treated with HNO3 in order to generate oxygen groups on the surface, while other supports were heat treated. Physical characterization of the catalyst was obtained using X-ray dispersive energy (EDX) and X-ray diffraction (XRD) techniques. Results showed that Pt-Ru catalysts with similar metal content (20%) and atomic ratios (Pt:Ru 1:1) were obtained. The electrochemical activity was studied by cyclic voltammetry and chronoamperometry. Higher methanol oxidation current densities were found for catalyst deposited on chemically treated supports. Electrode preparation and MEA assembly allowed an in-house built direct methanol fuel to be fitted with the synthesized catalysts and supports in order to assess their performance. Cell and reactants were conditioned by a direct methanol test station. Polarisation curves were measured and confirmed data obtained by voltammetry, regarding the effect of heat treatment of the carbon support. Normalised power curves per weight of catalyst are discussed in terms of the significant impact on noble metal loading and attained cell maximum power, in comparison with results obtained with a commercial catalyst.